2017
DOI: 10.1002/mop.30951
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth enhancement of a slot antenna with an open stub

Abstract: A method to increase the bandwidth of a slot antenna is proposed. Slot antennas are not widely used in mobile terminals because they have narrower bandwidth than conventional inverted F antennas. To increase the bandwidth, in this letter, a stub with one end connected to ground is inserted into the slot. The stub resonance is combined with the existing slot resonance and widens the antenna bandwidth. It is important to impedance matching at resonant frequencies of both slot and stub when feeding the antenna. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…On the other hand, they have a number of disadvantages, the most significant of which are low gain and limited bandwidth. As a result, numerous antenna researchers have made significant attempts to alleviate these limitations, such as by increasing bandwidth: increasing the thickness of the substrate [22], using stub [23], negative capacitor/inductor [24], Non-Foster Matching Circuit [25], and defected ground structures [26], magneto-dielectric substrates [27], electromagnetic band-gap (EBG) structures [28], and metamaterial resonators [29], using fractal geometries [30], and cavity backing [31]. The ever-increasing demand for wireless applications that deliver high-quality content to a large number of users simultaneously has resulted in a massive increase in data volume, which has resulted in a spectrum shortage in the microwave band, causing networks to become congested.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they have a number of disadvantages, the most significant of which are low gain and limited bandwidth. As a result, numerous antenna researchers have made significant attempts to alleviate these limitations, such as by increasing bandwidth: increasing the thickness of the substrate [22], using stub [23], negative capacitor/inductor [24], Non-Foster Matching Circuit [25], and defected ground structures [26], magneto-dielectric substrates [27], electromagnetic band-gap (EBG) structures [28], and metamaterial resonators [29], using fractal geometries [30], and cavity backing [31]. The ever-increasing demand for wireless applications that deliver high-quality content to a large number of users simultaneously has resulted in a massive increase in data volume, which has resulted in a spectrum shortage in the microwave band, causing networks to become congested.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, antenna array of broadband and wideband is also designed using different geometries for covering 5G bands 20–22 . Another antenna array of 5G coverage is designed using graphene materials 23 resonating at 3.51 GHz while stub‐ and slot‐loaded antenna for 2.4 GHz frequency using FR‐4 is presented for enhancing bandwidth 24 . Furthermore, another low‐profile antenna having two radiating patches with shorting pin is presented for bandwidth enhancement and minimized cross‐polarization 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Slot structures are commonly used to achieve bandwidth enhancement in multiband printed antennas. Traditional slot fractal shapes and other structures have been effectively used to design antennas with and multiband for a variety of wireless applications [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Sze et al [7] suggested a low profile dual-band Annular Ring Slot Antenna (ARSA) for the use in 2.4/5 GHz (WLANs).…”
Section: Introductionmentioning
confidence: 99%